Vremâ v bolgarskoj âzykovoj kartine mira - Аbramova, Valentina (Stylistyka, 2021)
The paper dwells on the phenomenon “time” in the Bulgarian language consciousness. The paper also focusis on the semantics and the use of lexims wich are connected with the segmentation of day and night.